2020
DOI: 10.1093/gerona/glaa192
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a On-site Medicalization Program for Nursing Homes With COVID-19 Outbreaks

Abstract: Background Nursing homes are highly vulnerable to the occurrence of COVID-19 outbreaks, which result in high lethality rates. Most of them are not prepared to SARS-CoV-2 pandemic. Methods A coordinated on-site medicalization program (MP) in response to a sizeable COVID-19 outbreak in four nursing homes was organized, with the objectives of improving survival, offering humanistic palliative care to residents in their natural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 25 publications
1
41
0
1
Order By: Relevance
“…We observed a significant overlap between the interactors of SARS-CoV-2 and ageing group. Further, we looked at a network-level scenario [35], by considering possible regulatory mechanisms that may be altered [42,43]. These observations support previous reports that SARS-CoV-2 may manifest in the blood leading to multiorgan failure in severe cases of COVID-19.…”
Section: Introductionsupporting
confidence: 72%
“…We observed a significant overlap between the interactors of SARS-CoV-2 and ageing group. Further, we looked at a network-level scenario [35], by considering possible regulatory mechanisms that may be altered [42,43]. These observations support previous reports that SARS-CoV-2 may manifest in the blood leading to multiorgan failure in severe cases of COVID-19.…”
Section: Introductionsupporting
confidence: 72%
“…Twelve studies reported hospitalization events for the confirmed COVID-19 residents from care homes. [ 11 , 26 , 39 , 44 , 49 , 52 , 53 , 55 , 58 , 59 , 66 , 68 ] None of the included studies reported information on clinical severity grade, rate of intensive care unit treatment, or invasive/non-invasive intervention following diagnosis. Overall, the rate of hospitalization amongst residents was 37% [95% CI 35–39%] for a total 2829 confirmed cases ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We found nine reports 3-11 supporting the concept of early multidrug pharmacological intervention can be used to improve clinical outcomes (the most important being reduction in death) in elderly nursing home residents suffering from COVID-19. We were focused on a high-risk group that typically worsens before treatment is administered within an in-patient hospital setting.…”
Section: Discussionmentioning
confidence: 87%
“…Bernabeu-Wittel et al reported from four nursing homes in Spain 3 that 272 of 457 (59.5%) residents contracted SARS-CoV-2 of whom 189 (69.5%) were given ‘active standard care’ and the rest were given advanced palliative care. For patients assigned to active standard care (i.e.…”
Section: Resultsmentioning
confidence: 99%